Kajian Proses Sintering pada Metode Metalurgi Serbuk Paduan Kobalt Sebagai Kandidat Material Implan Tulang - Aminatun, Aminatun (Jurnal Matematika dan Ilmu Pengetahuan Alam, 2015)
This study aimed to find out the optimum sintering temperature and time on the powder metallurgy method to produce cobalt alloy as candidate bone implants material. The quality of the metal alloy of the metallurgi method is determined by the temperature and time of sintering, resulting in the selection of these two parameters will be generated alloy which has a crystal structure as expected with better mechanical properties along with the crystal structure. The sintering process used powder metallurgy method with composition of 63.75 % Co - 30 % Cr - 5 % Mo - 0 , 5 % Mn - 0 , 5 % Si - 0 , 25 % N adjusted to ASTM F75. The initial step is all the ingredients of the milling process were mixed at a speed of 350 rpm for 15 minutes. Furthermore, powder was compressed with 21 MPa pressure at 200Â°C with 10 minutes holding time in the form of pellets with diameter of 1.5 cm. The pellet was sintered with temperature variations of 1100 ÂºC, 1200 ÂºC and 1300 ÂºC for 2 hours holding timeeach, and at a temperature of 1300 ÂºC with a variation of 1 hour and 3 hours holding time. The results showed that the crystal structure of the cobalt alloy contained 3 phase, which are phase Î³ (FCC), phase É (HCP), and Ï phase (tetragonal). Î³ phase appears at a temperature of 1300ÂºC with 1 and 2 hours holding time. The emergence of this Î³ -phase led to the increase of cobalt alloy hardness value, because Î³ âphase is a stable phase with a density greater than the other phases. The highest hardness value of 304.7 Â± 9.0VHN with the largest Î³-phase fraction (34.9 %) was obtained at a sintering temperature of 1300 ÂºC with 2 hours holding time. SEM - EDX test results indicated that cobalt alloys still contain pores or cavities with the uneven elements distribution and oxidation occurs. Based on these results it can be concluded that the sintering temperature of 1300 ÂºC with 2 hours holding time is the optimal sintering temperature and time to produce a cobalt alloy which has potential as bone implant material in terms of hardness value.Keywords: cobalt alloy, powder metallurgy, sintering